Dari Gotong Royong ke Pengupahan - Hasniah .; Safri . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2014)
This research aimed to identify and describe the changes of mutual assistance system to the wage system of farming society in the Alosika village. Data were collected by observation techniques involved participant observation and in-depth interviews. Data were analyzed by descriptive qualitative. Data analysis was intended to simplify the data obtained in order to be read and understood by the younger. The results showed that the change from mutual aid system to the wage system of the farmer society in Alosika village was socio-cultural changes that came from government programs. The entry of the transmigration program in the village had caused the change of local societies chosen from the rice farm fields with a form of agriculture as a group, switch to traditional rice farming. Likewise with the ground, beside as means of production, it was also as assets and investation tools for farmers in the Alosika village. The mindset of rice farmers in the Alosika village that promote effectiveness and efficiency in order to achieve maximization of profit, had led farmers in the village to be more creative in developing their agricultural systems. Farmers then know the wage system which was then applied to the agricultural system as a substitute for mutual assistance system that was considered had harmed the farmers. The need for money had a very large role of agricultural system and socio cultural changing order in the Alosika village among farmers, because farmers had to think about the gains and losses in agricultural fields. Keywords: mutual assistance, wages, farmers